Gun violence is a public health crisis that needs more applied criminologists - Braga, Anthony Allan (Criminology & public policy, 2022)
Research Summary Gun violence was declared a "public health crisis" after shootings increased in many U.S. cities during the course of the COVID-19 pandemic. The public health approach to gun violence prevention offers many advantages such as an applied research model, the mobilization of a wider range of stakeholders, and a commitment to harm reduction. Too often, however, the public health community seems unaware of criminological research on gun violence and avoids including criminal justice interventions in their comprehensive plans. Policy Implications Communities need immediate relief from the persistent trauma of repeated shootings. Criminal justice interventions represent important responses to outbreaks of gun violence that should be included among recommended public health programs intended to address proximate and upstream causes of gun violence. Gun violence prevention policy and practice would be strengthened by more deliberate attempts to foster complementary public health and criminology research and development collaborations. More applied criminologists need to become engaged in gun violence research to meet this call.